2019
DOI: 10.1038/s41598-019-44651-z
|View full text |Cite
|
Sign up to set email alerts
|

Water properties under nano-scale confinement

Abstract: Water is the universal solvent and plays a critical role in all known geological and biological processes. Confining water in nano-scale domains, as encountered in sedimentary rocks, in biological, and in engineered systems, leads to the deviations in water’s physicochemical properties relative to those measured for the non-confined phase. In our comprehensive analysis, we demonstrate that nano-scale confinement leads to the decrease in the melting/freezing point temperature, density, and surface tension of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
178
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(188 citation statements)
references
References 47 publications
8
178
0
2
Order By: Relevance
“…The effective thickness h of the interfacial water layer is limited by a few nanometers 12,36 . Therefore, the enhanced conductivity of confined water observed in our experiment can be explained by the cumulative effect of the interfacial water with high ionic conductivity σi, and the water with bulk conductivity σw 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The effective thickness h of the interfacial water layer is limited by a few nanometers 12,36 . Therefore, the enhanced conductivity of confined water observed in our experiment can be explained by the cumulative effect of the interfacial water with high ionic conductivity σi, and the water with bulk conductivity σw 37 .…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that extreme confinement of ILs can lead to a change of the freezing-melting temperature. The change in the melting point of a liquid in a confined geometry is described by the Gibbs-Thomson equation [64], which usually accounts for the depression of the freezingmelting point of the liquid (as in the case of water [65]) into a pore. This equation predicts a reduction of the freezing-melting temperature inversely proportional to the pore dimension and proportional to the difference Δγ=γ wl −γ ws between the wall-liquid surface energy γ wl and the wall-solidified liquid surface energy γ ws .…”
Section: The Effect Of Confinement On the Structural Properties Of Iomentioning
confidence: 99%
“…recently showed that the water existing in nanoscale confinement behaves more like ice in a mesoporous silica system. Due to increased impact of surface water‐silanol interactions, the ice like effects are more significant when mesopores are smaller than 5 nm . Therefore, high transverse relaxivity of mesoporose silica coated iron carbide NPs can be explained by the effect of hydrophilic mesoporous shell which increases the capability of trapping large amounts of ice‐like water with high T 2 relaxation rate …”
Section: Resultsmentioning
confidence: 99%